2018
DOI: 10.1111/scs.12618
|View full text |Cite
|
Sign up to set email alerts
|

Recovery, symptoms, and well‐being one to five years after lung transplantation – A multi‐centre study

Abstract: Background In recent years, survival after lung transplantation has remained largely unchanged despite improvements in short‐and intermediate‐term survival, indicating the need to identify factors associated with recovery and long‐term survival. Very little is known about how lung recipients recover after lung transplantation and whether such factors are related to symptom distress and well‐being. This constitutes the rationale of the study. Aim The aim was to explore symptom prevalence and distress as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…The findings are confirmed by Lundmark et al, where a majority of lung transplant recipients experienced several symptoms and restrictions 1 to 5 years posttransplant but still reported good well-being and general health. 10 Another study revealed that the majority of lung transplant recipients experienced considerable improvement in physical health and well-being, despite reporting physical complaints and restrictions in everyday life. 12 It was concluded that adjusting to posttransplant life required acceptance of ongoing illness and that health-care providers should act as mediators to facilitate the journey to relative normalcy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings are confirmed by Lundmark et al, where a majority of lung transplant recipients experienced several symptoms and restrictions 1 to 5 years posttransplant but still reported good well-being and general health. 10 Another study revealed that the majority of lung transplant recipients experienced considerable improvement in physical health and well-being, despite reporting physical complaints and restrictions in everyday life. 12 It was concluded that adjusting to posttransplant life required acceptance of ongoing illness and that health-care providers should act as mediators to facilitate the journey to relative normalcy.…”
Section: Discussionmentioning
confidence: 99%
“…The findings are confirmed by Lundmark et al, where a majority of lung transplant recipients experienced several symptoms and restrictions 1 to 5 years posttransplant but still reported good well-being and general health. 10 Another study revealed that the majority of lung transplant recipients experienced considerable improvement in physical health and well-…”
Section: Reflections On the Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…119 To this end, Singer et al 120 published preliminary validation of a LTx-specific HRQoL survey that assesses symptoms, health perceptions, functional status, and well-being. Separately, Lundmark et al 121 analyzed the impact of objective lung function on subjective outcomes. Interestingly, they found no correlation between lung function and self-reported recovery or well-being.…”
Section: Mechanical Circulatory Support (Mcs) Magouliotis Et Almentioning
confidence: 99%